The Role of Social Media Analytics in Predicting Green Consumer Behavior: A Conceptual Framework - Bilgah Bilgah; Andrianto, Usman; Rastryana, Ulta; Kiswati, Sri; Maryoso, Slamet (Brilliant International Journal Of Management And Tourism, 2026)
This study proposes a conceptual framework to examine the role of social media analytics in predicting green consumer behavior. As sustainability becomes increasingly important in consumer decision-making, social media has emerged as a powerful tool for influencing attitudes and behaviors. The framework suggests that social media engagement, measured through analytics such as likes, shares, comments, and sentiment, influences green attitudes, environmental awareness, and green purchase intentions, which ultimately affect consumer behavior. Additionally, the study highlights that generational differences, environmental concern, and trust in green claims moderate these relationships. The proposed model builds upon existing theories in consumer behavior and sustainability marketing, offering new insights into how digital engagement shapes green consumer choices. From a practical perspective, this framework provides guidance for marketers to leverage social media analytics in promoting sustainable consumption, especially by tailoring strategies to different generational segments. Future research should empirically test the framework, explore its applicability across diverse cultural contexts, and examine the role of emerging social media platforms in fostering sustainable consumer behavior.